Preserving Authenticity and Integrity of Distributed Networks through Novel Message Authentication Code - Gurpreet K. Sodhi; Gurjot S. Gaba; Lavish Kansal; Eduard Babulak; Mohammed AlZain; Sandeep Kumar Arora; Mehedi Masud (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In this era of universal electronic connectivity, communication is no more confined to transfer of data from one end to the other; rather it aims at secure data transfer. Communication sector has developed beyond this traditional boundary of data transfer and is now working on ways to provide data from the intended senders to the intended receivers in an unaltered form. Considering all these conditions, the data transfer needs to follow the principles of authentication, confidentiality and integrity. The former two have been addressed using digital signatures and encryption schemes respectively, while the solution to the later is the use of Message Authentication Code. This paper presents a Message Authentication Code scheme, which uses the biological characteristics represented by Deoxyribonucleic acid combined with the output of Blum Blum Shub Random Number Generator, as a secret key along with a novel hash algorithm. This Message Authentication Code structure is evaluated on the basis of National Institute of Science and Technology test suite for random numbers, avalanche criteria and network attacks. The results reveal that the proposed scheme performs well under all the criteria and thus is capable of preserving integrity; this increases its applicability in any data sensitive environment.